Studi Validitas dan Reliabilitas Mindfulness in Teaching Scale Indonesia - Khairani, Rullyta Nadia; Cahyadi, Surya; Susanto, Hery (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study was aimed to examine the validity and reliability of the Mindfulness in Teaching Scale in Indonesia (MTS-I). This research was a quantitative research. Data were collected from teachers of elementary, secondary, and high school in Bandung (n=244) using convenience sampling. Confirmatory factor analysis (CFA) was conducted to test the two factor structures of MTS-I, Pearson product moment to test concurrent validity, and Cronbach’s alpha to test the internal consistency. Results confirmed the validity and reliability of the model. MTS-I had the same structure with the original one. MTS-I had 13 valid and reliable items which were divided into two dimensions, interpersonal mindfulness and intrapersonal mindfulness. MTS-I demonstrated construct validity with good-fit index. Furthermore, regarding concurrent validity, positive correlations were obtained between MTS-I subscales with teacher efficacy, and negative correlations were obtained between MTS-I subscales with teacher stress.